Clinical evaluation of bonded amalgam restorations in endodontically treated premolar teeth - H Moosavi; M Nojoomian; F Ahrari (Isfahan University of Medical Sciences, 2008)
Introduction: There are controversies about the clinical efficiency of bonded amalgamrestprations. The aim of this clinical study was comparison of fracture resistance, marginaladaptation and recurrent caries in endodontically-treated premolar teeth.Methods and Materials: Thirty five patients with endodontically treated upper first or secondpremolars were selected and divided into three groups. Copalite varnish in group A, Amalgambond plus in group B and Scotchbond Multi Purpose in group C were applied as a sealer. The teethin all three groups were restored with intracanal pin and amalgam in combination with lingualcusp coverage. After 1 year, fracture resistance, marginal adaptation and secondary caries wereevaluated. Fischer's exact test was used for statistical analysis (& = 0.05).Results: There was no significant difference among groups with respect to fracture resistance(p value = 0.3). Significant differences in marginal adaptation existed between the three groups(p value = 0.01). No recurrent caries were found in clinical and radiographic evaluation ofrestored teeth.Conclusion: In one-year clinical period, using Amalgam bond Plus or Scotchbond Multi Purposeas dentine bondings to bond complex amalgam restorations in endodontically treated premolarteeth, there was no increase in fracture resistance of restorations and teeth and this treatment hadno effect on prevention of recurrent caries, but resulted in significant improvement in marginaladaptation.Key words: Bonding agent, fracture resistance, marginal adaptation, recurrent caries